Research Project Entitled "Success and Failure of the Entrepreneurs-A Study of Underlying Factors" - Planning Commission (Planning Commission, 1995)
A small scale unit as an agent of self employment has been defined in terms of investment in plant and machinery. Prior to 1975 village and small industries sector covered undertakings having investment in plant and machinery not exceeding Rs. 7.5 lakhs and in the case of ancillary units Rs. 10 lakhs. The limits of investment have been revised upwards from time to time. Thus in 1975, it was raised to Rs. 10 lakhs for a small scale unit and Rs. 15 lakhs for an ancillary unit. In 1980, it was further raised to Rs. 20 lakhs and Rs. 25 lakhs respectively.
Planning Commission Government of India
Planning Commission Government of India